Globalisasi Ekonomi dan Tantangannya terhadap Ekonomi Politik Islam - Bella Permata Sari; Devika Putriani; Diva Oktanadia; Rama Harfi Ferdinan; Sendy Setia Ardifta; Hotman Hotman (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
Economic globalization is a process that significantly impacts the structure and values within Islamic political economy. Market integration, trade liberalization, and cross-border capital flows have created an increasingly competitive and capitalistic global economic order. On one hand, globalization provides opportunities for developing countries, including Indonesia, to access new technologies, expand export markets, and increase foreign investment. However, on the other hand, globalization also poses serious challenges for Islamic political economy, particularly due to the dominance of capitalist principles that contradict the fundamental values of Islamic economics, such as justice ('adl), balance (tawazun), and the prohibition of riba and gharar. Additionally, internal challenges such as low community literacy, a lack of innovation in Sharia-compliant financial products, and insufficient policy support further hinder the development of the Islamic economy. This research employs a descriptive qualitative method based on literature studies to analyze the impact of globalization on Islamic political economy. The findings indicate that adaptive strategies, innovation enhancement, regulatory strengthening, and the improvement of literacy and research are necessary for Islamic political economy to play a strategic role in addressing the challenges of globalization. Thus, it is hoped that Islamic political economy can contribute to the realization of a more just and sustainable global economic order.